An Efficient Disinfectant, Composite Material {SLS@[Zn3(CitH)2]} as Ingredient for Development of Sterilized and Non Infectious Contact Lens - V.A. Karetsi; C.N. Banti; N. Kourkoumelis; C. Papachristodoulou; C.D. Stalikas; C.P. Raptopoulou; V. Psycharis; P. Zoumpoulakis; T. Mavromoustakos; I. Sainis; S.K. Hadjikakou (MDPI AG, 2019)
The [Zn3(CitH)2] (1) (CitH4= citric acid), was dispersed in sodium lauryl sulphate (SLS) to form the micelle of SLS@[Zn3(CitH)2] (2). This material 2 was incorporated in hydrogel made by hydroxyethyl-methacrylate (HEMA), an ingredient of contact lenses, toward the formation of pHEMA@(SLS@[Zn3(CitH)2]) (3). Samples of 1 and 2 were characterized by UV-Vis, 1H-NMR, FT-IR, FT-Raman, single crystal X-ray crystallography, X-ray fluorescence analysis, atomic absorption and TG/DTA/DSC. The antibacterial activity of 1−3 as well as of SLS against Gram-positive (Staphylococcus epidermidis (St. epidermidis) and Staphylococcus aureus (St. aureus)) and Gram-negative (Pseudomonas aeruginosa (PAO1), and Escherichia coli (E. coli)) bacteria was evaluated by the means of minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and inhibitory zone (IZ). 2 showed 10 to 20-fold higher activity than 1 against the bacteria tested. Moreover the 3 decreases the abundance of Gram-positive microbes up to 30% (St. aureus) and up to 20% (PAO1) the Gram-negative ones. The noteworthy antimicrobial activity of the obtained composite 3 suggests an effective antimicrobial additive for infection-free contact lenses.